The third class genie - Leeson,Robert (Collins London, 2000)
Alec's world changes when he meets Abu the genie! Disasters were leading two-nil on Alec's disaster-triumph scorecard when he slipped into the vacant factory lot, with Ginger Wallace hot on his heels, ready to destroy him. There was a catastrophe awaiting him at home too, and of course school was yet another disaster area. But his luck seemed to be changing when he discovered a sealed beer can that was obviously empty. Stranger still, when he held it up to his ear, he could hear a faint snoring ..